Divergent effects of vitamins K1 and K2 on triple negative breast cancer cells - Beaudin, Sarah (Oncotarget, 2019)
Vitamin K serves as an essential co-factor in the γ-carboxylation of glutamate to γ-carboxyglutamate (GLA), a post-translational modification mediated by gamma-glutamyl carboxylase (GGCX) and vitamin K oxidoreductases (VKORC1 or VKORC1L1). While both phylloquinone (K1) and menaquinone (K2) support the synthesis of GLA-modified proteins, studies assessing K1 and/or K2 effects in cancer cells have reported minimal effects of K1 and anti-proliferative or pro-apoptotic effects of K2. qPCR results indicated highest expression of GGCX, VKORC1, and VKORC1L1 in triple negative breast cancer (TNBC) cell lines, Hs578T, MDA-MB-231 and SUM159PT, and in advanced stage disease. To assess differential effects of vitamin K, TNBC cells were cultured in media supplemented with K1 or K2. K1 treatment increased cell growth, and enhanced stemness and GLA-modified protein expression in TNBC lysates. Alternatively, lysates from cells exposed to vehicle, K2, or the VKOR antagonist, warfarin, did not express GLA-modified proteins. Further, K2 exposure reduced stemness and elicited anti-proliferative effects. These studies show that TNBC cells express a functional vitamin K pathway and that K1 and K2 exert distinct phenotypic effects. Clarification of the mechanisms by which K1 and K2 induce these effects may lead to relevant therapeutic strategies for manipulating this pathway in TNBC patients.